CULTURAL LIFE IN THE BUKHARA EMIRATE - Umar Kuziyevich Ergashev (European Science Publishing, 2024)
The Bukhara Emirate, which existed from the 18th to the early 20th century, was a significant cultural and intellectual center in Central Asia. Situated along the Silk Road, Bukhara served as a melting pot of Islamic, Central Asian, Persian, and Turkic cultures. Its religious and intellectual life was deeply intertwined with Islamic scholarship, particularly in the fields of jurisprudence, theology, and mysticism. The city was home to renowned madrasas, such as the Mir-i-Arab Madrasa, and the Naqshbandi Sufi order, which had a profound influence on the region. Bukhara also flourished in literature, producing notable poets such as Alisher Navoi, and in the arts, particularly in calligraphy, miniature painting, and manuscript illumination. The city’s architecture, characterized by grand mosques, madrasas, and monumental structures, blended Persian, Turkic, and Central Asian styles. In addition to its intellectual and artistic contributions, daily life in Bukhara was marked by a rich tradition of music, dance, and cultural exchange, driven by its position as a key stop on the Silk Road. Despite the eventual decline of the emirate, Bukhara’s legacy continues to influence Central Asian culture today.
Keywords: Bukhara Emirate, cultural life, Islamic scholarship, Naqshbandi Sufi order, literature, Alisher Navoi, calligraphy, miniature painting, architecture, Silk Road, Central Asia, religious institutions, madrasas, daily life, music, dance, Persian influence, Turkic influence.